The Hermeticism in Suhrawardi's Illumination Theology - Zhang, Yi (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2025)
Hermeticism is one of the world's oldest religious and philosophical traditions, primarily distributed in the Mediterranean region. Shihab al-Din Yahya al-Suhrawardi is a renowned Muslim scholar in Iran and a notable Illuminationist (ishraqi). The most representative aspect of Suhrawardi's Islamic theology is his Illumination Theology (Ḥikmat al-Ishraq), which also forms the foundation of his Islamic theology. In previous research by scholars worldwide, examining the origins of Suhrawardi's thought has become a very important topic. Many experts and religious scholars have studied this and yielded significant findings. However, these discussions seem to have overlooked the fact that Suhrawardi's thought has Hermetic origins. Here, the author will employ the qualitative method of close reading of texts, focusing on comparing Suhrawardi's works with Hermetic texts, and integrating relevant research to explore the Hermeticism contained within Suhrawardi's llumination Theology. The focus is on how Hermeticism influenced Suhrawardi's Illumination Theology and how Suhrawardi's Illumination Theology transformed Hermeticism. This study will reveal the relationship between the theological thought of Muslim scholars, and even Islamic theology, and ancient intellectual heritage.